Reporter cell lines to evaluate the selectivity of chemicals for human and zebrafish estrogen and peroxysome proliferator activated γ receptors - Grimaldi, Marina; Boulahtouf, Abdelhay; Delfosse, Vanessa; Thouennon, Erwan; Bourguet, William; Balaguer, Patrick (Frontiers in Neuroscience, 2015)
Zebrafish is increasingly used as an animal model to study the effects of environmental nuclear receptors (NRs) ligands. As most of these compounds have only been tested on human NRs, it is necessary to measure their effects on zebrafish NRs. Estrogen receptors (ER) α and β and peroxysome proliferator activated receptor (PPAR) γ are main targets of environmental disrupting compounds (EDCs). In humans there are two distinct nuclear ERs (hERα and hERβ), whereas the zebrafish genome encodes three ERs, zfERα, zfERβ1 and zfERβ2. Only one isoform of PPARγ is expressed in both humans and zebrafish. In this review, we described reporter cell lines that we established to study the interaction of EDCs with human and zebrafish ERs and PPARγ. Using these cell lines, we observed that zfERs are thermo-sensitive while zfPPARγ is not. We also showed significant differences in the ability of environmental and synthetic ligands to modulate activation of zfERs and zfPPARγ in comparison to hERs and hPPARγ. Some environmental estrogens (bisphenol A, mycoestrogens) which are hER panagonists displayed greater potency for zfERα as compared to zfERβs. hERβ selective agonists (8βVE2, DPN, phytoestrogens) also displayed zfERα selectivity. Among hERα selective synthetic agonists, 16α-LE2 was the most zfERα selective compound. Almost all zfPPARγ environmental ligands (halogenated bisphenol A derivatives, phthalates, perfluorinated compounds) displayed similar affinity for human and zebrafish PPARγ while pharmaceutical hPPARγ agonists like thiazolidones are not recognized by zfPPARγ. Altogether, our studies show that all hERs and hPPARγ ligands do not control in a similar manner the transcriptional activity of zfERs and zfPPARγ and point out that care has to be taken in transposing the results obtained using the zebrafish as a model for human physiopathology.